2023
DOI: 10.1002/advs.202206243
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Advanced Cellulosic Triboelectric Materials via Dielectric Modulation

Abstract: The rapid rise of triboelectric nanogenerators (TENGs), which are emerging energy conversion devices in advanced electronics and wearable sensing systems, has elevated the interest in high-performance and multifunctional triboelectric materials. Among them, cellulosic materials, affording high efficiency, biodegradability, and customizability, are becoming a new front-runner. The inherently low dielectric constant limits the increase in the surface charge density. However, owing to its unique structure and exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 358 publications
(422 reference statements)
0
12
0
Order By: Relevance
“…The dielectric constants of the PLA-based membranes gradually increased with the addition of Zn-TIO, increasing from 0.82 F/m for pure PLA to 1.30 F/m for PLA/Zn-TIO-10, in direct proportion with the surface potential. It is revealed that the dielectric property of the polymer material is an influencing factor shaping the interaction of PMs and the fiber surface, as well as the charge storage abilities of the electrospun electret filters. As illustrated in Figure d, the increase in the dielectric constant is accompanied by significant promotion of the surface potential. It indicates that the improved dielectric properties of the PLA NFMs with the increase of the Zn-TIO contents were primarily responsible for the largely increased surface potential of the PLA composite membranes …”
Section: Resultsmentioning
confidence: 99%
“…The dielectric constants of the PLA-based membranes gradually increased with the addition of Zn-TIO, increasing from 0.82 F/m for pure PLA to 1.30 F/m for PLA/Zn-TIO-10, in direct proportion with the surface potential. It is revealed that the dielectric property of the polymer material is an influencing factor shaping the interaction of PMs and the fiber surface, as well as the charge storage abilities of the electrospun electret filters. As illustrated in Figure d, the increase in the dielectric constant is accompanied by significant promotion of the surface potential. It indicates that the improved dielectric properties of the PLA NFMs with the increase of the Zn-TIO contents were primarily responsible for the largely increased surface potential of the PLA composite membranes …”
Section: Resultsmentioning
confidence: 99%
“…39 It is of interest that there is a linear relationship between the dielectric constant and the initial surface potential (Figure 3d), meaning that the significant increase in the initial surface potential could be closely associated with the increase in the dielectric constant. Moreover, the high dielectric properties also indicate the high "charge affinity" of selfpowered PLA NFMs, 40 which likely contributes to the improvement of the triboelectric properties. It is worth emphasizing that the molecular electrostatic surface potential (ESP) showed that the C�O dipoles on the surface of PLA chains exhibited negative potentials (Figure 3e), which are responsible for the negative values of surface potentials of PLA FMs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Energy harvesting from mechanical vibrations 1,2 or biomechanical movements 3 using eco-friendly energy-harvesting technologies has inspired considerable research enthusiasm in convenient environmental energy collection and electrical energy conversion. 4,5 Nanogenerators (NGs), including triboelectric 6 (TE) NGs and piezoelectric 7 (PE) NGs, are potentially convenient and efficient energy harvesting schemes that have extensive applications as sustainable power sources for small-scale portable electronic devices 8 due to their advantages of simple implementation mechanism, 9 convenient manufacturing process, 10 diverse material selections, 11 and abundant structural designs. 12 To effectively convert distributed low-frequency mechanical energy 13 into usable electricity, TENGs usually separate opposite polarity charges originating from the contact of different substances through the TE effect 14 based on the coupling of contact electrification and electrostatic induction, while the electricity in PENGs originates from the mechanical deformation 15 of the PE material between two electrodes.…”
Section: Introductionmentioning
confidence: 99%